Islamic Religious Education Pattern of the Urgency of Healthy Food for Students at State Elementary School 14 South Pontianak - Khair, Fathul (Journal of English Language and Education, 2026)
This study aims to describe the pattern of Islamic Religious Education (PAI) in instilling the urgency of healthy food consumption in students at SD Negeri 14 South Pontianak. Islamic religious education at the elementary school level not only focuses on the formation of moral and religious character, but also integrates health values through the concept  of halalan thayyiban as part of Islamic teachings. This study uses a qualitative approach with a descriptive method. Data was obtained through observation of the PAI learning process, interviews with PAI teachers and students, and documentation of various school habituation programs. The results of the study show that PAI teachers apply an integrative learning pattern through strengthening material on halal food, thayyib, and eating manners in Islam. Teachers combine interactive lecture methods, discussions, examples, and habituation through the Healthy Canteen program, appeals to bring nutritious provisions, and supervision of snack consumption in the school environment. Students show an increased understanding of the characteristics of healthy food and begin to implement more selective eating behaviors. This study concludes that the pattern of PAI in SD Negeri 14 South Pontianak contributes significantly to fostering students' awareness of the importance of healthy food, both from a religious and physical health perspective, thereby supporting the formation of healthy character and lifestyle from elementary school age.